Why Have the Republic of Korea, Taiwan, and Singapore Coped Well with COVID-19 and What Are the Lessons Learned from Their Experiences? - Kim, Jaewan; Moon, Jongwoo; Jung, Tae Yong; Kim, Woojin; Yoo, Herim Clara (Yonsei medical journal, 2022)
This study investigated how three Asian countries-Republic of Korea (ROK), Republic of China (Taiwan), and Singapore-considered as standouts, responded to the coronavirus disease 2019 (COVID-19) in terms of governance system, health sector innovation, and social distancing to draw lessons that other countries can learn from. The countries were commonly in success of the response in early stage of the pandemic thanks to their effective and efficient strategies paired with advanced information and communications technology (ICT). Consequently, the three jurisdictions reported lower confirmed cases as well as fatality rate of the infectious disease compared to other high-income countries. In addition, the countries' previous experiences with other pandemics, including influenza A, Middle East respiratory syndrome, and severe acute respiratory syndrome, enabled them to establish resilient public health systems and gain public acceptance to governmental control or surveillance during national infectious disease-related crises outbreaks. Advanced ICT infrastructure and digital technology were used as effective tools for testing, tracing, and treatment of the pandemic in collaboration with the private sector as a crucial player. The ROK, Taiwan, and Singapore adopted different strategies between containment and mitigation policy to flatten the epidemic curves effectively according to their own situation and judgement. Despite the exemplary aspect of the three nations in coping with the COVID-19 pandemic, a few limitations were also observed in terms of vaccination and unequal consequences of the pandemic among people. These should be further discussed in order to be prepared for future pandemics.